Efektivitas kombinasi pembatasan kalori dan kapsul kacang kedelai (Glycine max) terhadap kadar trigliserida pada individu obesitas usia 25-45 tahun - Hanifah Mardhotillah; Al Rivan Marsyah Dzikri; Fitriani Ekawati (Poltekkes Kemenkes Aceh, 2026)
Background: Obesity is significantly associated with lipid metabolism disorders, one of which is characterized by elevated triglyceride levels that may lead to cardiovascular complications. Caloric restriction is a commonly applied non-pharmacological approach for managing obesity; however, its effectiveness may be enhanced when combined with functional foods, such as soybeans, which are rich in bioactive compounds.Objectives: This study aimed to evaluate the effects of caloric restriction combined with soybean capsule consumption on triglyceride levels in individuals with obesity.Methods: This study was conducted in Kuningan, West Java, using a single-blind randomized controlled trial with a pre-post design over 14-day period. Thirty individuals with obesity were randomly assigned to two groups. The control group underwent caloric restriction of 1800 kcal/day, whereas the intervention group received the same caloric restriction along with 3000 mg/day soybean capsules. Triglyceride levels were measured before and after the intervention. Data were analyzed using parametric and non-parametric tests according to the data distribution, with a 95% confidence interval (CI), complemented by effect size analysis using Cohen’s d.Results: The intervention group demonstrated a significantly greater reduction in triglyceride levels than that in the control group (p = 0.004). The mean decrease in triglyceride levels was 5.9±3.9 mg/dL in the intervention group, whereas the control group showed a reduction of 3.13±1.64 mg/dL. Cohen’s d value of 0.93 indicated a large effect size.Conclusion: The combination of caloric restriction and soybean capsules for 14 days resulted in a more significant reduction in triglyceride levels than caloric restriction alone. These findings suggest a potential short-term metabolic benefit in individuals with obesity.